Absorption of chemicals in amorphous trisresorcinarene. Issue 83 (18th September 2020) - Shimoyama, Daisuke; Sekiya, Ryo; Haino, Takeharu
Abstract : Trisresorcinarene is an interesting class of macrocyclic host. Its unique structure and insolubility allow to function as a amorphous solid absorbent capable of absorbing various aromatic and aliphatic hydrocarbons. Abstract : Trisresorcinarene is an interesting class of macrocyclic host. Its insoluble nature and conformationally flexible structure allow its application as a solid absorbent. Various aromatic and aliphatic hydrocarbons are absorbed into the amorphous solid of the trisresorcinarene, demonstrating the versatile absorption capability of trisresorcinarene.